Impact of oil prices on the Singapore economy - Tan, Cheow Nam (2008)
This paper examines the impact of the change in the oil price on the growth of the Singapore economy, using GDP growth as the primary proxy, retrospectively through the last several decades. The results how that oil price increases led to higher GDP growth in Singapore. This impact has been increasing even though the share of petroleum export in total domestic export is declining.